Performance and satisfaction level among Chilean physical therapy students regarding the use of online problem-based learning (OPBL) in the pathophysiology course. - Figueroa-González, Paola; Viera-López, Mauricio; Gómez-Miranda, Luis; Gutiérrez-Arias, Ruvistay; Contreras-Pizarro, Viviana; Riquelme-Bravo, Paula; Díaz-Cabrera, Armando (Revista Facultad de Medicina de la Universidad Nacional de Colombia, 2025)
Introduction: Online problem-based learning (OPBL) has been used to train health professionals, but there is limited evidence on student performance and satisfaction following its implementation. Objective: To evaluate the performance of Chilean physical therapy students taking a pathophysiology course after implementing OPBL and to determine their level of satisfaction with this methodology. Materials and methods: A retrospective, analytical, observational study was conducted on 106 second-year physical therapy students at a university in Santiago, Chile, enrolled in the pathophysiology course during the second semester of 2021. The students were divided into 30 groups, each with 2 to 6 members, and the intervention consisted of solving two clinical problems (OPBL1 and OPBL2) with a 5-week work period for each OPBL (4 weeks of group work and 1 week of evaluation). The differences in the scores obtained and the passing rate in the oral presentation (group evaluation), the individual written test, the self-evaluation rubric, and the differences in the co-evaluation rubric between OPBL1 and OPBL2 were analyzed using the Wilcoxon signed-rank test and the chi-square test. Results: Participants were aged between 19 and 23 years and 50.95% were female. Regarding performance in the individual written test, it was found that the median score in OPBL1 was 13 points (p25-p75: 11-14) and 32.08% passed, while the median score in OPBL2 was 9 points (p25-p75: 7-12) and 15.09% passed. In the group evaluation (30 groups), the median score was 62.5 points (p25-p75: 59-67) in OPBL1 and 62.5 points (p25-p75: 60-67) in OPBL2, and the passing rate was 96.67% in OPBL1 and 100% in OPBL2. Concerning students' satisfaction with the use of this methodology in the course, most of them selected "agree" (24.53-39.62%) and "strongly agree" (35.85-55.56) in the evaluated items. Conclusions: The students achieved their learning objectives in the pathophysiology course, so it can be concluded that their performance was adequate after implementing the OPBL, highlighting that group performance was superior to individual performance. Moreover, the level of student satisfaction with the use of this methodology was high.